Effect of a 308‐nm excimer laser on atopic dermatitis‐like skin lesions in NC/Nga mice. Issue 6 (13th April 2016) - Oh, Chang Taek; Kwon, Tae‐Rin; Seok, Joon; Choi, Eun Ja; Kim, Soon Re; Jang, Yu‐Jin; Mun, Seog Kyun; Kim, Chan Woong; Lee, Sungeun; Lee, Jongmin; Kim, Myeung Nam; Choi, Sun Young; et al.
Abstract : Background and Objective: Atopic dermatitis (AD) is a common inflammatory skin disease that can affect all age groups. It has a relapsing course, which dramatically affects the quality of life of patients. A 308‐nm excimer laser has been reported to be a safe and effective treatment for inflammatory skin diseases, although the range of potential application has not been fully explored. The purpose of this study was to evaluate the therapeutic effects of a 308‐nm laser on AD‐like skin lesions in NC/Nga mice. Study Design/Materials and Methods: Dermatophagoides farinae ‐exposed NC/Nga mice with a clinical score of 12 were treated with either a 308‐nm excimer laser or narrowband‐UVB (NB‐UVB). The effects of the 308‐nm excimer laser were evaluated by dermatitis scores, skin histology, skin barrier function, and immunological parameters, including IgE and Th2‐mediated cytokines. Results: The 308‐nm excimer laser significantly reduced the severity of skin lesions and decreased the total serum levels of IgE and Th2‐mediated cytokines. The excimer laser also significantly reduced the inflammatory cellular infiltrate into AD‐induced skin lesions. Moreover, treatment with the 308‐nm excimer laser led to recovery of skin barrier function in AD‐induced skin lesions. Conclusion: The 308‐nm excimer laser can be considered a valid and safe therapeutic option for the treatment of localized AD. Lasers Surg. Med. 48:629–637, 2016. © 2016 Wiley Periodicals, Inc.